2018
DOI: 10.3389/fmed.2018.00018
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Protein D in Respiratory and Non-Respiratory Diseases

Abstract: Surfactant protein D (SP-D) is a multimeric collectin that is involved in innate immune defense and expressed in pulmonary, as well as non-pulmonary, epithelia. SP-D exerts antimicrobial effects and dampens inflammation through direct microbial interactions and modulation of host cell responses via a series of cellular receptors. However, low protein concentrations, genetic variation, biochemical modification, and proteolytic breakdown can induce decomposition of multimeric SP-D into low-molecular weight forms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
142
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(165 citation statements)
references
References 498 publications
(633 reference statements)
4
142
2
4
Order By: Relevance
“…SPD is predominantly produced in type 2 pneumocytes and is also expressed in the endothelium of the cardiovascular system, acting as a mediator on inflammatory signals. 40 SPD has been associated in longitudinal studies with an increase of cardiovascular mortality in COPD patients. 41 CC-16 are secreted mainly in the terminal portion of the bronchioles and their plasma levels are inversely associated with an increase in mortality in COPD.…”
Section: Serum Biomarkersmentioning
confidence: 99%
“…SPD is predominantly produced in type 2 pneumocytes and is also expressed in the endothelium of the cardiovascular system, acting as a mediator on inflammatory signals. 40 SPD has been associated in longitudinal studies with an increase of cardiovascular mortality in COPD patients. 41 CC-16 are secreted mainly in the terminal portion of the bronchioles and their plasma levels are inversely associated with an increase in mortality in COPD.…”
Section: Serum Biomarkersmentioning
confidence: 99%
“…Thus, in patients with the first group in all three observation points, the data obtained were higher relative to the levels of SP-D of the second group, which is related to the influence of hypertension as a factor that characterizes the higher severity of the systemic and local inflammatory response during acute processes, defining injuries pulmonary tissue [19]. The study by Grith L Sorensen and co-authors showed the presence of SP-D in endothelial cells and its involvement in modulating the local inflammatory response [20], which in turn indicates the feedback of the effect of the development of the process of inflammation in the lungs caused by bacterial agents [21] on the possible complications of concomitant arterial hypertension.…”
Section: Discussion Of the Resultsmentioning
confidence: 95%
“…Several lung diseases like-asthma, acute respiratory distress syndrome (ARDS), COPD etc. are reported to be associated with aberration in the functionalities of surfactant proteins [70,106]. In SARS-CoV-2 affected lung, production of the surfactant proteins are found to be deregulated (Figure 8) Considering all these, lung surfactants might be useful in the treatment of COVID-19 patients, as lung surfactant replacement therapies were previously reported to be successful in other respiratory infections and acute lung injury to reduce the lung damage of the patients [104,108,109] and also our analysis found it as an alternative from enrichment of related process deregulated genes (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Host miRNAs miR-421 are found to be downregulating LMCD1; while miR-137, miR-375, miR-429 fail to modulate CCDC59 and GATA6 because of their probable inactivation/suppression by differential expression of its regulating TFs (Figure 8). As SFTPD and SFTPC are downregulated along with several regulatory partners, their primary function of immunomodulation and efficient air exchange in lung [68,69] might be seriously hindered by the viral proteins; which could further lead to abnormal pathogenic lung injury [70].…”
Section: Sars-cov-2 Proteins and Host Epigenetic Regulators Can Modulmentioning
confidence: 99%